Contribuição ao estudo de planejamento automático aplicado a sistema de movimentação de materiais - Cardoso, Rodrigo Nogueira (2014)
In the transporting of loads, the container loading problems have had much repercussion among logistical studies. It can be proved that through using such device there is a reduction on losses, theft, damaging of goods and general costs. The loading problems are typical optimization problems whose objective is maximizing the used volume or minimize the costs parameters. On the other hand, automated planning research, a sub area of artificial intelligence, intends to assist the industrial processes for systematically specifying a set of actions that allows achieving a predefined goal. In this paradigm the industrial plant is modeled with a series of diagrams respecting the UML standard, for obtaining the problem domain and the initial and final states. It is noteworthy that in the actions specifying process a metric can be added for minimizing purposes, but according to each automated planners characteristics the insertion of such metrics is relatively bounded. In an attempt to accrete both areas of knowledge, it is intended to use one of the widely studied techniques available in the loading problem literature, in particular the linear programming for modeling and the Simplex method for solving, in a way to obtain a specific final state to be utilized in the automated planning solving process. The main proposal of this integration is to create a fully automated system, capable of carrying out the entire loading process through the information referred to the products, to the industrial plant and the transporting devices.